If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 32 = (x + -7)(x + 7) Reorder the terms: 32 = (-7 + x)(x + 7) Reorder the terms: 32 = (-7 + x)(7 + x) Multiply (-7 + x) * (7 + x) 32 = (-7(7 + x) + x(7 + x)) 32 = ((7 * -7 + x * -7) + x(7 + x)) 32 = ((-49 + -7x) + x(7 + x)) 32 = (-49 + -7x + (7 * x + x * x)) 32 = (-49 + -7x + (7x + x2)) Combine like terms: -7x + 7x = 0 32 = (-49 + 0 + x2) 32 = (-49 + x2) Solving 32 = -49 + x2 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x2' to each side of the equation. 32 + -1x2 = -49 + x2 + -1x2 Combine like terms: x2 + -1x2 = 0 32 + -1x2 = -49 + 0 32 + -1x2 = -49 Add '-32' to each side of the equation. 32 + -32 + -1x2 = -49 + -32 Combine like terms: 32 + -32 = 0 0 + -1x2 = -49 + -32 -1x2 = -49 + -32 Combine like terms: -49 + -32 = -81 -1x2 = -81 Divide each side by '-1'. x2 = 81 Simplifying x2 = 81 Take the square root of each side: x = {-9, 9}
| 5(6c-4)+3(8c-1)= | | 2(3+5x)-5=31 | | 74-4x=14x+24 | | 15-2(w+5)=11 | | X+24=130 | | 11x-31=-20 | | x+9.8=14.5 | | 7=y-12 | | 3x-17=16-(2x+8) | | 2x+12=90+3x+23 | | 30x+3=123 | | 16x+420=-100 | | 7-2=13-3 | | 4(y+3)+7=4y+19 | | 22=5x+7 | | X^3-2x^2+5x-1=0 | | 6+2f=20-3f | | 3(y+6)=2(y+4) | | 18[m+0.44]-16=118 | | 4(3x-8)=16 | | -102+7x=7x+24 | | 2x+x^2-35=0 | | x-3.7=3.5 | | -14(3a+6)=12(6-4a)+12 | | 3(y-7)=21 | | 8x-2=94 | | 2(s+1)=12 | | 8p+3=23 | | 9+7r=13 | | 5+5y=25 | | 4(x-3)=-16-1 | | 15=y-13 |